Inter-chromosomal transcription hubs shape the 3D genome architecture of African trypanosomes - Claudia Rabuffo; Markus R. Schmidt; Prateek Yadav; Pin Tong; Roberta Carloni; Anna Barcons-Simon; Raúl O. Cosentino; Stefan Krebs; Keith R. Matthews; Robin C. Allshire; T. Nicolai Siegel (Nature Communications)
Abstract The eukaryotic nucleus exhibits a highly organized 3D genome architecture, with RNA transcription and processing confined to specific nuclear structures. While intra-chromosomal interactions, such as promoter-enhancer dynamics, are well-studied, the role of inter-chromosomal interactions remains poorly understood. Investigating these interactions in mammalian cells is challenging due to large genome sizes and the need for deep sequencing. Additionally, transcription-dependent 3D topologies in mixed cell populations further complicate analyses. To address these challenges, we used high-resolution DNA-DNA contact mapping (Micro-C) in Trypanosoma brucei, a parasite with continuous RNA polymerase II (RNAPII) transcription and polycistronic transcription units (PTUs). With approximately 300 transcription start sites (TSSs), this genome organization simplifies data interpretation. To minimize scaffolding artifacts, we also generated a highly contiguous phased genome assembly using ultra-long sequencing reads. Our Micro-C analysis revealed an intricate 3D genome organization. While the T. brucei genome displays features resembling chromosome territories, its chromosomes are arranged around polymerase-specific transcription hubs. RNAPI-transcribed genes cluster, as expected from their localization to the nucleolus. However, we also found that RNAPII TSSs form distinct inter-chromosomal transcription hubs with other RNAPII TSSs. These findings highlight the evolutionary significance of inter-chromosomal transcription hubs and provide new insights into genome organization in T. brucei.